Nitric oxide modulation in neuroinflammation and the role of mesenchymal stem cells - Pan, M. Liy; A. Puzi, Nur Nabilah; Jose, Shinsmon; Vidyadaran, Sharmili (Society for Experimental Biology and Medicine, 2021)
Nitric oxide is a versatile mediator formed by enzymes called nitric oxide synthases. It has numerous homeostatic functions and important roles in inflammation. Within the inflamed brain, microglia and astrocytes produce large amounts of nitric oxide during inflammation. Excessive nitric oxide causes neuronal toxicity and death and mesenchymal stem cells can be used as an approach to limit the neuronal damage caused by neuroinflammation. Mesenchymal stem cell therapy ameliorates inflammation and neuronal damage in disease models of Alzheimer’s disease, Parkinson’s disease, and other neuroinflammatory disorders. Interestingly, we have reported that in vitro, mesenchymal stem cells themselves contribute to a rise in nitric oxide levels through microglial cues. This may be an undesirable effect and highlights a possible need to explore acellular approaches for mesenchymal stem cell therapy in the central nervous system.